A Subjective Academic Narrative: Practice-Led Research and Indigenous postgraduate opportunities - Josie Jacqueline Arnold (Institute of Advanced Engineering and Science, 2013)
The methodology of this paper continues the work I have done writing the ‘subjective academic narrative’ for publication within refereed academic journals. Storytelling is a basic human activity and the academy since the mid 20th century has begun to see its value rather than use it as the non-academic side of the dichotomy between thought and reason and feeling and emotion that the Enlightenment left as its residue of academic thought and knowledge. I use this methodology to enter into the privileged academic discussion and to add to it regarding the relationship of Indigenous knowledge to the academy that remains a challenge in Australian Universities in this postmodern and postcolonial moment. This paper recognises the need to open discussion about how Indigenous people might be facilitated within the academy to bring their knowledge-models into the university and its traditional dominant knowledge systems. This paper looks at Practice Led Research (PLR) as a possible pathway for supporting the transition of Indigenous community scholars into university postgraduate courses. It explores how PLR contributes to an appropriate entry point into postgraduate studies for some Indigenous students who have significant life experiences and narratives and/or productions of artefacts that act to replace the breadth of undergraduate credentials. This paper identifies and explicates a nexus between Practice Led Research and Recognition of Prior Learning (RPL) and Recognition of Current Competencies (RCC). In doing so, it provides a reference point for University protocols and practices regarding RPL and RCC.DOI: http://dx.doi.org/10.11591/ijere.v2i1.1715